First Charge Exchange Recombination Spectroscopy Diagnostic in HL-2A Tokamak - 韩晓玉 段旭如 杨立梅 余德良 钟武律 傅炳忠 刘永 刘仪 严龙文 杨青巍 (Chinese physics letters, 2010)
Spatially resolved measurements of ion temperature are crucial for understanding plasma dynamics. A charge exchange recombination spectroscopy diagnostic system based on a heating neutral beam is installed on the HL- 2A tokamak. An optical collection system is designed in accordance with the actual geometry of HL-2A and the CVI 529.2nm （n = 8 → 7） charge-exchange recombination line. Preliminary measurements show that the CX signals have enough signal-to-noise ratio （SNR）. The ion temperature and its profiles are obtained through this svstem for the first time.